The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.7863/jum.1999.18.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasonography in the assessment of organic diseases of female urethra.

Abstract: The current investigation aimed to check the effectiveness of transvaginal ultrasonography in the diagnosis of organic urethral diseases, comparing its results with those of conventional examinations (physical examination, voiding cystourethrography, pelvic ultrasonography, cystourethroscopy). Transvaginal ultrasonography was performed in 560 female patients with recurrent cystitis, dysuria, or palpable masses and diagnosed the following urethral diseases: 25 diverticula, seven stenoses, three carcinomas, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…In the present series, 11 women had their urethral pressure profile assessed and of these, only six had the classical biphasic curve associated with a UD [8,9]. Ultrasonography of the urethra can be either transvaginal, transperineal or transurethral [10–12]; whilst all these methods can visualize a periurethral lesion they are all operator‐dependent and it can be difficult to differentiate between a UD and other cystic lesions. Initial studies supported this [11], although a more recent study suggested that ultrasonography may be as effective as VCUG for identifying UD, but more effective than VCUG for visualizing the diverticular neck [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the present series, 11 women had their urethral pressure profile assessed and of these, only six had the classical biphasic curve associated with a UD [8,9]. Ultrasonography of the urethra can be either transvaginal, transperineal or transurethral [10–12]; whilst all these methods can visualize a periurethral lesion they are all operator‐dependent and it can be difficult to differentiate between a UD and other cystic lesions. Initial studies supported this [11], although a more recent study suggested that ultrasonography may be as effective as VCUG for identifying UD, but more effective than VCUG for visualizing the diverticular neck [12].…”
Section: Discussionmentioning
confidence: 99%
“…This exam permitted the diagnosis of large diverticula without communication with the urethral lumen and palpable mass effect and provided a complete evaluation of anatomical risk factors, like size, contents, shape and location [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…D'autre part, elle nécessite des manipulations qui peuvent être source de traumatisme urétral ou d'infection [2]. L'échographie transvaginale peut aussi être un examen rentable dans le diagnostic de pathologie urétrale [3]. L'IRM pelvienne est beaucoup plus performante pour définir l'anatomie et la complexité du diverticule, elle permet de préparer l'intervention chirurgicale d'autant plus que la reconstruction urétrale peut être difficile, en particulier en cas de diverticule circonférentiel [4].…”
Section: Discussionunclassified